Experiences of pregnant adolescent girls - Maseko, Vella (My University, 2008)
ABSTRACT This study sought to explore the experiences of pregnant adolescent learners. It solicited information around challenges faced by pregnant adolescent girls, the impact of pregnancy on interpersonal relationships and psychological functioning, the support system that pregnant learners have, as well as their current feelings and perceptions about their experience. It is a qualitative study, and it employed thematic content analysis to analyse the results. The sample, comprising of five adolescent girls, was drawn purposively from Soweto High Schools. Adolescent pregnancy is generally perceived as a social problem because of the negative consequences often associated with it. Literature also suggests that low socio-economic circumstances and developmental factors predispose adolescents to a higher risk for unplanned pregnancy. The results of this study indicate that an experience of pregnancy during adolescence often results in challenges that may have a negative impact on normative development. Another finding is that most adolescent mothers receive very little or no financial and emotional support from families, partners or formal structures.
Keywords: adolescents; girls; causes; consequences; pregnancy; early parenting